Pengaruh Gaya Hidup dan Literasi Keuangan terhadap Minat Investasi Kelompok Pekerja di Daerah Sedati Sidoarjo - Wiguna, Enrico Adya; Pudjianto, Agung; Mulyati, Diana Juni (Research Journal of Social Science and Economics, 2025)
This study aims to examine the effect of lifestyle and financial literacy on the interest in investing in a group of workers in the Sedati Region, Sidoarjo. Lifestyle and financial literacy have an important role in shaping individual financial behavior, including their interest in investing. The research method used was a survey using questionnaires distributed to groups of workers in the Sedati area, Sidoarjo. The research sample consisted of 96 respondents who are randomly selected from a group of workers in the Sedati area, Sidoarjo. The results of the study show that there is a significant influence between lifestyle and financial literacy on the investment interest of the working group. These findings indicate that a lifestyle that tends to manage finances wisely and has adequate knowledge about investing tends to have a higher interest in investing. This research has important implicit in the development of financial literacy and investment education programs in the Sedati Region, Sidoarjo. It is hoped that the government and related institutions can provide training programs and relevant information to increase financial literacy and increase awareness of the benefits of investment for workers in the Sedati Region, Sidoarjo.